The Effect of Parental Educational Expectations on Adolescent Subjective Well-Being and the Moderating Role of Perceived Academic Pressure: Longitudinal Evidence for China - Haiyang Lu; Peng Nie; Alfonso Sousa-Poza (Institute of Labor Economics (IZA), 2019)
Although the strong positive correlation between parental educational expectations (PEE) and child academic achievement is widely documented, little is known about PEE's effects on child psychological outcomes and the mechanisms through which it may work. Hence, in this paper, using nationally representative data from the 2013-2014 and 2014-2015 waves of the China Education Panel Survey, we investigate PEE's causal impact on adolescent subjective well-being (SWB) and the moderating role of the academic pressures that these adolescents perceive. Even though we find robust evidence for a positive causal relation between PEE and adolescent SWB, its moderation by adolescent-perceived academic pressure is negative. In addition, the facts that the benefits of PEE are greater for female adolescents and those from immigrant, one-child, and nonpoor families suggests that it may operate on adolescent SWB through increased family resources, improved family relationships, and higher adolescent aspirations linked to higher PEE.
Keywords: I21; I30; J13; 330; China; parental educational expectations; adolescents; subjective well-being